Somatotype and body composition of elite brazilian gymnasts - Ferreira João, A.; Fernandes Filho, J. (Science of Gymnastics Journal, 2015)
The main objective of this study was to analyze the somatotype and body composition of elite athletes in Brazilian artistic gymnastics ,belonging to the junior an dsenior categories. Forty-six athletes were assessed, whereby 21 were from Male Artistic Gymnastics and 25 from Female Artistic Gymnastics. To determine the somatotype, the Heath& Carter's anthropometric method was used(1990).The body composition was assessed by electrical bioimpedance on the InBody R20 scale,and variables of skeletal muscle mass (MM), fat mass( MG), fat-free mass (MLG) and fat percentage (%G) were measured. Descriptive statistics was used. Results show that the dominant somatotype within the group of male gymnasts was the Balanced mesomorph while among the females, the prevalent classification was Ectomorphic mesomorph. The body composition of the male gymnasts presented the average values of 33.08±3.53 kg for lean muscle mass,7.44± 1.57 kg for fat mass, 57.74±5.78 kg for fat-free mass and a fat percentage of 11.39±2.08, while the female gymnasts showed values of 21.7±3.38 kg for lean body mass, 7.55±2.73 kg for fat mass, 38.12±5.77 kg for fat-freemass and a fat percentage of 15.84±3.79. These results corroborate with the existing profiles for the modality of artistic gymnastics found in literature.